The evolution of hog production and potential sources for future growth in China - Xiao, H.; Wang, J.; Oxley, Leslie; Ma, H. (2012)
Following reforms to the market, China's hog industry has developed rapidly, however, with social and economic transitions, China's hog industry is facing challenges which might restrict long-term growth in production. This paper analyzes the changes in regional scale, organization, input factors, and technological progress for China's hog production over the last few decades. The paper seeks to reveal the sources of hog production growth and provide some suggestions for future development of the hog industry. To achieve these aims, the paper uses stochastic frontier production functions and the Malmquist index to measure total factor productivity (TFP) in the hog industry and decompose TFP into technical efficiency; technological progress; scale efficiency; and allocative efficiency using data for 25 provinces from 1980 to 2008. The results show firstly that; the TFP of hog production increased by 64.3% from 1980 to 2008, and allocative efficiency and scale efficiency improvements played a key role in this TFP growth. In contrast, technical efficiency and technical progress have changed little over this period. Secondly, TFP's contribution to output was 39.7%, it being less than that of factor inputs to output. Thirdly, the results suggest that the growth of China's pork production depends mostly on the increase in the quantity of factor inputs, especially feed. As a consequence, the key to ensuring long-term and stable development of China's hog production would seem to involve focusing on enhancing total factor productivity and changing the pattern of production growth. © 2012 Elsevier Ltd.